Membangkitkan energi diri (self-power) Ahmad Salim Badawilan ; penerjemah Irham Sya roni ; editor Zainul Arifin El-Basyier - BADAWILAN, Ahmad Salim; El-Basyier, Zainul Arifin; Sya'roni, Irham (2010)
325 hlm 20 cm